Perancangan Sistem Informasi Pengawasan Lapangan Berbasis Web pada Balai Pembangunan Jalan Nasional (BPJN) Aceh - Al-Wafi, Muhammad Ghifari; Nurrizqa; Zahra, Rita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
In the era of globalization and advancements in information technology, government agencies in Indonesia are required to adapt to technological developments to improve work effectiveness and efficiency. This research aims to design a web-based information system to support field monitoring at BPJN Sub-Field PPK 2.1 Aceh. The system is designed to meet user needs by providing features such as real-time data input, project progress monitoring, detailed reporting, and quick and accurate information access. The design and development method used is the Waterfall model, which includes a step-by-step process starting from requirement analysis, system design, program coding, program testing, and program implementation. The results of the study indicate that the designed web-based information system can enhance the efficiency and effectiveness of field monitoring. The new system shows significant improvements in data collection speed, data accuracy, work efficiency, and ease of data access. Testing using the black-box method shows that the system works well according to the designed functions. With the adoption of this information technology, BPJN Sub-Field PPK 2.1 Aceh is expected to improve operational efficiency, reduce errors, and enhance the quality of infrastructure project monitoring.